1780 Mass. Const. art. XVII, pt. 1 - (:unkn) unknown (My University, 1780)
Declared a right to bear arms for the common defense, and that standing armies are dangerous to liberty in times of peace and shall not be maintained without the consent of the legislature.
Keywords: GUARANTEED RIGHT